Polyaniline / nano-silver composite material and preparation method thereof, low-temperature slurry and heterojunction battery
By using polyaniline/nanosilver composites to prepare low-temperature slurry, the problem of large consumption of silver paste for heterojunction battery electrodes is solved, the silver content is reduced and the conductivity is improved, and cost reduction and performance improvement is achieved.
Patent Information
- Application Number
- CN202411961716.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
Due to its double-sided structure, the consumption of electrode silver paste is larger than that of conventional crystalline silicon batteries, resulting in higher costs. At the same time, the doping efficiency of existing conductive polymers is low, affecting the conductivity.
Polyaniline/nanosilver composite material is used to form a first reaction system by mixing aniline monomer, an acidic reaction medium and an oxidizing agent to obtain polyaniline, and then a third reaction system is formed with a doped acid and a silver source to obtain a polyaniline/nanosilver composite material. The composite material is used to prepare low-temperature slurries, reducing silver content and improving conductivity.
The melting point and silver content of the slurry are reduced, the conductivity and stability of the slurry are improved, so that the slurry can be cured at lower temperatures, reducing electrode costs and improving the performance of heterojunction batteries.
Smart Images

Figure BDA0005217329420000211
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell manufacturing, and in particular to a polyaniline / nano-silver composite material and a preparation method thereof, a low-temperature slurry and a heterojunction battery. Background Art
[0002] The full name of heterojunction cell is crystalline silicon heterojunction solar cell. It is a special PN junction formed by amorphous silicon and crystalline silicon materials. This technology is to deposit amorphous silicon thin film on crystalline silicon. It combines the advantages of crystalline silicon cells and thin film cells and is considered to be one of the important development directions of high conversion efficiency silicon-based solar cells. Due to the symmetrical structure of heterojunction cells, it brings a natural advantage of double-sided power generation. But at the same time, silver paste is required to form the electrodes for both the front and back electrodes of the battery. Compared with conventional crystalline silicon cells that only use front silver and back silver paste, the consumption of silver paste for heterojunction battery electrodes is greater than that of conventional crystalline silicon cells due to the double-sided structure. Therefore, the most effective way to reduce the cost of heterojunction cells is to reduce the cost of electrodes.
[0003] Conjugated double bond conductive polymers play an indispensable role in industrial applications due to their semiconductor and metal-like conductivity, as well as the advantages of low cost and simple process. Using them as conductive additives to prepare low-temperature slurries can greatly reduce costs. In order to achieve high-performance conductive polymers, suitable dopants are usually selected to fully react with polymers to achieve efficient electron transport and increase the carrier concentration in the main chain. However, the doping efficiency of most conductive polymers is currently low (usually around 10%), which has an adverse effect on conductivity. Summary of the invention
[0004] In order to overcome the above problems, the present invention aims to provide a polyaniline / nanosilver composite material and a preparation method thereof, a low-temperature slurry and a heterojunction battery. The composite material is used to prepare a low-temperature slurry, which can reduce the melting point of the slurry, improve the slurry's guiding property, and reduce the silver content in the slurry.
[0005] In order to achieve the above object, the present invention provides a method for preparing a polyaniline / nanosilver composite material, the preparation method comprising:
[0006] Aniline monomer, an acidic reaction medium, and an oxidant are mixed to form a first reaction system, and a first reaction is performed to obtain polyaniline;
[0007] mixing polyaniline with a doping acid to form a second reaction system, and performing a second reaction to obtain modified polyaniline;
[0008] The modified polyaniline is mixed with a first dispersant and a reducing agent, and then a silver source is added to form a third reaction system, and a third reaction is performed to obtain a polyaniline / nanosilver composite material (PANI / AgNPs).
[0009] In the above preparation method, in the first reaction, the acidic reaction medium can improve the reactivity of the aniline monomer. The acidic reaction medium may include one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid, and hypophosphorous acid.
[0010] In the above preparation method, the molar ratio of the acidic reaction medium to the aniline monomer can be 0.1-1:1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 and other specific values, as well as a range with any two of the above specific values as endpoints.
[0011] In some specific embodiments, the acidic reaction medium may be added in the form of a solution, and the concentration of the solution of the acidic reaction medium may be 0.1 M-1 M. In the present invention, the unit M is mol / L.
[0012] In the above preparation method, in the first reaction, the oxidant can initiate polymerization of aniline monomer to form polyaniline. The oxidant may include one or a combination of two or more of hydrogen peroxide, ammonium persulfate, ammonium peroxide, and potassium chlorate.
[0013] In the above preparation method, the molar ratio of the aniline monomer to the oxidant can be 0.1-1:1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 and other specific values, as well as a range with any two of the above specific values as endpoints.
[0014] In the above preparation method, the molecular formula of the aniline monomer is:
[0015] In the above preparation method, the temperature of the first reaction can be controlled to be -1°C to 10°C, for example, specific values such as -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, and ranges with any two of the above specific values as endpoints; the time of the first reaction can be controlled to be 1h-15h, for example, specific values such as 1h, 3h, 6h, 9h, 12h, 15h, and ranges with any two of the above specific values as endpoints.
[0016] According to a specific embodiment of the present invention, the preparation method may further include vacuum filtering, washing and drying the product of the first reaction to obtain polyaniline. The cleaning agent used for the washing may include deionized water, ethanol (which may be anhydrous ethanol), methanol (which may be anhydrous methanol), acetone, or a combination of two or more thereof. The drying temperature may be 50-100° C., and the drying time may be 1 h-24 h.
[0017] In the above preparation method, in the second reaction, the doping acid has the following functions: the doped proton acid decomposes to produce H + The anions and counter anions enter the main chain and combine with the N atoms in the amine and imine groups to form polar and dipole delocalized into the P bonds of the entire molecular chain, thereby making the polyaniline conductive. The doping acid may include one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid, and hypophosphorous acid.
[0018] In the above preparation method, the mass ratio of the doping acid to the polyaniline can be 0.01-1:1, for example, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 006:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.5:1, 1:1 and other specific values, and ranges with any two of the above specific values as endpoints. In some specific embodiments, the mass ratio of the doping acid to the polyaniline can be further controlled to be 0.01-0.08:1, and further can be 0.01-0.06:1.
[0019] In the above preparation method, the doping acid may be added in the form of a solution, and the concentration of the doping acid solution may be 0.1M-1M.
[0020] In the above preparation method, the temperature of the second reaction is 25°C-55°C, for example, specific values such as 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, and a range with any two of the above specific values as endpoints; the time of the second reaction is 1h-24h, for example, specific values such as 1h, 4h, 8h, 12h, 16h, 20h, 24h, and a range with any two of the above specific values as endpoints.
[0021] According to a specific embodiment of the present invention, the preparation method may further include vacuum filtering and drying the product of the second reaction, and the modified polyaniline obtained may be in a powder state. The drying temperature may be 50-100° C., and the drying time may be 1 h-24 h.
[0022] In the above preparation method, the silver source may include one or a combination of two or more of silver chloride, silver nitrate, and potassium silver cyanide.
[0023] In the above preparation method, the silver source may be added in the form of a solution, and the concentration of the silver source solution may be 0.1M-1M.
[0024] In the above preparation method, the mass ratio of the modified polyaniline to the silver source can be 0.1-1:1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 and other specific values, as well as a range with any two of the above specific values as endpoints.
[0025] In the above preparation method, the first dispersant may include one or a combination of two or more of polyvinyl pyrrolidone, polyvinyl alcohol, and sodium dodecyl sulfate.
[0026] In the above preparation method, the mass of the first dispersant is 1%-7% of the mass of the silver source, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7% and other specific values, and a range with any two of the above specific values as endpoints.
[0027] In the above preparation method, the reducing agent may include one or a combination of two or more of sodium borohydride, hydrazine hydrate, glucose, ascorbic acid, sodium hypophosphite, and tannic acid.
[0028] In the above preparation method, the molar ratio of the reducing agent to the silver source is (0.5-3):1, for example, specific values such as 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, and a range with any two of the above specific values as endpoints.
[0029] In the above preparation method, the temperature of the third reaction is 25-80°C, for example, specific values such as 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, and ranges with any two of the above specific values as endpoints; the time of the third reaction is 1h-10h, for example, specific values such as 1h, 2h, 4h, 6h, 8h, 10h, and ranges with any two of the above specific values as endpoints.
[0030] According to a specific embodiment of the present invention, the modified polyaniline can be first dispersed into the oxidant and the first dispersant, and then the silver source is added dropwise thereto to form a third reaction system. In a specific embodiment, the dispersion process can be carried out by ultrasound to achieve a uniform dispersion effect.
[0031] According to a specific embodiment of the present invention, the preparation method may further include vacuum filtering or centrifuging, washing, and drying the product of the third reaction to obtain a polyaniline / nanosilver composite material. The cleaning agent used for the cleaning includes one or a combination of two or more of deionized water, anhydrous ethanol, methyl ether, and acetone. The drying temperature may be 50-100° C., and the drying time may be 1 h to 24 h.
[0032] The preparation method of the polyaniline / nanosilver composite material provided by the present invention improves the conductive properties of the polymer by modifying the conductive polymer. The metal nanoparticles are introduced into the conductive polymer to improve the performance. The metal nanoparticles distributed in the polymer matrix can improve the conductivity and environmental stability, and can also improve the problem of easy agglomeration of the nanoparticles.
[0033] The invention also provides a polyaniline / nano-silver composite material, which is obtained by the above preparation method.
[0034] The nano silver / polyaniline of the present invention belongs to a conductive polymer composite material (CPC), which is a composite material composed of a polymer and a conductive filler, and can conduct heat and electric charge. Compared with traditional metal conductors, they have many advantages. The polymer matrix in CPCs has flexibility, low cost and low density. Among the numerous conductive fillers, metal fillers are the most advantageous because they have high conductivity, and silver and gold are not easily oxidized at high temperatures, but the price of a single metal is relatively high. By combining the metal and the polymer matrix, optimal functionality and economic efficiency can be achieved.
[0035] In the polyaniline / nano-silver composite material of the present invention, nano-silver particles gradually accumulate in the polyaniline matrix, so that the gaps between polymer chains become smaller or even connected, and the exciton transition band gap on the polyaniline chain structure ring is enlarged, thereby widening the carrier transport path and improving the carrier transmission efficiency. Nano-silver particles are in an energy unstable state due to their large surface energy, so that fine particles tend to gather together and are easy to agglomerate. Polyaniline plays a role in supporting nano-silver, making it well dispersed and not easy to agglomerate. The metal-conductive polymer composite material not only retains the respective advantages, but also reduces the agglomeration, and gives full play to the synergistic effect between the components. The metal-conductive polymer composite material is used as a conductive auxiliary agent to prepare a low-temperature slurry, so that the conductivity and stability of the conductive electrode after the slurry is completely solidified are good, and the conductivity can be improved while reducing the silver content. Since the melting point of the composite material is low, the slurry can be solidified within 200°C.
[0036] The present invention provides a low-temperature slurry, which, based on the total mass of the low-temperature slurry being 100%, comprises:
[0037] Micro-nano powder: 72%-87%;
[0038] Organic binder: 1%-3.8%;
[0039] PANI / AgNPs additive: 5%-20%;
[0040] Solvent: 1%-3.2%;
[0041] Additives: 0.1%-1%;
[0042] Wherein, the PANI / AgNPs additive includes the above-mentioned polyaniline / nanosilver provided by the present invention.
[0043] The low-temperature slurry contains the polyaniline / nano-silver composite material of the present invention. The synergistic effect of the nano-silver and polyaniline in the additive enhances the stability of the slurry system and reduces the curing temperature. In addition, the polyaniline / nano-silver composite material is used to construct a good three-dimensional conductive network in the slurry system, thereby improving the conductive performance of the slurry and reducing the silver content.
[0044] In the above-mentioned low-temperature slurry, the mass content of the PANI / AgNPs additive in the low-temperature slurry is generally 5-20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% and other specific values, and a range with any two of the above specific values as endpoints; further, it can be 5%-15%.
[0045] In the above-mentioned low-temperature slurry, the mass content of the micro-nano powder in the low-temperature slurry is generally 72%-87%, for example, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87% and other specific values, and a range with any two of the above specific values as endpoints; further, it can be 77%-87%.
[0046] In the above-mentioned low-temperature slurry, the micro-nano powder includes one or a combination of two or more of micro-nano spherical silver powder, micro-nano flaky silver powder and micro-nano silver-coated copper powder.
[0047] In the above low-temperature slurry, the specific surface area of the micro-nano spherical silver powder is 0.4-0.6m 2 / g, D 50 1.9-2.3μm.
[0048] In the above low temperature slurry, the surface area of the micro-nano flaky silver powder is 0.55-0.8m 2 / g, D 50 2.8-3.3μm.
[0049] In the above low-temperature slurry, the tap density of the micro-nano silver-coated copper powder is 2.8-5.4 g / cm 3 , D 50 4.2-5.7μm.
[0050] In the above-mentioned low-temperature slurry, the organic binder may include one or a combination of two or more of phenolic resin, thermoplastic polyurethane, epoxy resin, silicone resin, urea-formaldehyde resin and acrylic resin.
[0051] In the above-mentioned low-temperature slurry, the mass content of the organic binder in the low-temperature slurry is generally 1%-3.8%, for example, specific values such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 3.8%, and a range with any two of the above specific values as endpoints.
[0052] In the above-mentioned low-temperature slurry, the solvent includes one or a combination of two or more of terpineol, butyl carbitol, butyl carbitol acetate, dioctyl phthalate, dibasic acid ester, ethylene glycol butyl ether, diethylene glycol monomethyl ether, and isophorone.
[0053] In the above-mentioned low-temperature slurry, the mass content of the solvent in the low-temperature slurry is generally 1%-3.2%, for example, specific values such as 1%, 1.5%, 2%, 2.5%, 3%, 3.2%, and a range with any two of the above specific values as endpoints.
[0054] In the above-mentioned low-temperature slurry, the auxiliary agents include a curing agent, a coupling agent, a leveling agent and a second dispersant.
[0055] In the above-mentioned low-temperature slurry, the curing agent includes one or more combinations of imidazole curing agents, amine curing agents, and acid anhydride curing agents. In some specific embodiments, the imidazole curing agent may include one or more combinations of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-isopropylimidazole, 2-ethylimidazole, etc.; the amine curing agent may include one or more combinations of ethylenediamine, hexamethylenediamine, diethylenetriamine, benzyldiamine, metaphenylenediamine, triethanolamine, N,N-diethylaminopropylamine, etc.; the acid anhydride curing agent may include one or more combinations of styrene anhydride, maleic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, maleic anhydride, methyltetrahydrophthalic anhydride, pyromellitic anhydride, etc.
[0056] The coupling agent includes one or a combination of two or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, bistriethanolamine diisopropyl titanate, and neoalkoxy tris(p-aminophenoxy) zirconate.
[0057] In the above-mentioned low-temperature slurry, the leveling agent includes one or a combination of two or more of polyether, polyorganosiloxane, polydimethylsiloxane, turpentine, and polyacrylic acid.
[0058] In the above low-temperature slurry, the second dispersant includes one or a combination of two or more of oleic acid, stearic acid, ethyl acetoacetate, butyrylacetone, polyethylene glycol, hydrogenated castor oil, and polyamide wax.
[0059] In the above-mentioned low-temperature slurry, the mass content of the additive in the low-temperature slurry is generally 0.1%-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and other specific values, as well as a range with any two of the above specific values as endpoints.
[0060] The present invention also provides a method for preparing the low-temperature slurry, which comprises:
[0061] The micro-nano powder, organic binder, solvent, auxiliary agent and additive are mixed, stirred, and placed in a vacuum degassing machine for stirring (the stirring speed may be 2500 rpm, and the stirring time may be 2 minutes); and ground and dispersed to obtain the low-temperature slurry.
[0062] The present invention also provides a heterojunction battery, which is made of the above-mentioned low-temperature slurry.
[0063] The beneficial effects of the present invention include:
[0064] 1. The polyaniline / nano silver composite material provided by the present invention is a metal-conductive polymer composite material obtained by utilizing a conductive polymer modification technology. In this composite material, nano silver particles gradually accumulate in a polyaniline matrix, so that the gap between the polymer chains becomes smaller or even connects, and the exciton transition band gap on the polyaniline chain structure ring expands, thereby widening the carrier transport path and improving the transmission efficiency of the carrier. Nano silver particles are in an energy unstable state because of their large surface energy, so that fine particles all tend to gather together and are easy to reunite. The metal-conductive polymer composite material not only retains advantages separately, but also reduces cohesion, and gives full play to the synergistic effect between the components.
[0065] 2. The low-temperature slurry provided by the present invention is a low-temperature curing slurry with high conductivity. The slurry is prepared using the above-mentioned polyaniline / nanosilver composite material as a conductive filler. While reducing the silver content in the slurry, the conductivity of the slurry is also improved, the line resistance and contact resistance are reduced, and the conductivity and stability of the conductive electrode after the slurry is completely cured are good; due to the low melting point of the composite material, the slurry can be cured within 200°C. DETAILED DESCRIPTION
[0066] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0067] In the following examples and comparative examples, the specific surface area of the spherical silver powder used is 0.4-0.6 m 2 / g、D 50 The surface area of the silver flake powder used is 0.55-0.8m 2 / g、D 50 The tap density of the silver-coated copper powder used is 2.8-5.4g / cm 3 , D 50 4.2-5.7μm.
[0068] Example 1
[0069] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0070] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0071] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0072] Metal powder (i.e. micro-nano powder): 52.2% flaky silver powder, 34.8% spherical silver powder;
[0073] Organic binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0074] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0075] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0076] PANI / AgNPs additive: 5%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0077] The specific method includes: weighing the corresponding raw materials according to the mass percentage, mixing the metal powder, organic binder, solvent, auxiliary agent and additive, first stirring manually, and then putting it into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing it through a three-roll mill for 6 times to obtain a low-temperature slurry.
[0078] Example 2
[0079] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0080] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0081] This embodiment also provides a low-temperature slurry, and based on the mass of the low-temperature slurry being 100%, its raw material composition includes:
[0082] Metal powder: 49.2% flake silver powder, 32.8% spherical silver powder;
[0083] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0084] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0085] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0086] PANI / AgNPs additive: 10%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0087] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0088] Example 3
[0089] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0090] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0091] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0092] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0093] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0094] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0095] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0096] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0097] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0098] Example 4
[0099] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0100] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0101] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0102] Metal powder: 46.2% flake silver powder, 30.8% spherical silver powder;
[0103] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0104] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0105] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0106] PANI / AgNPs additive: 15%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0107] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0108] Example 5
[0109] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0110] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0111] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0112] Metal powder: 44.4% flake silver powder, 29.6% spherical silver powder;
[0113] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0114] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0115] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0116] PANI / AgNPs additive: 18%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0117] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; and finally grinding and dispersing by a three-roll mill for 6 times.
[0118] Example 6
[0119] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0120] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0121] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0122] Metal powder: 43.2% flake silver powder, 28.8% spherical silver powder;
[0123] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0124] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0125] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0126] PANI / AgNPs additive: 20%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0127] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0128] Comparative Example 1
[0129] This comparative example provides a low-temperature slurry, and based on the mass of the low-temperature slurry being 100%, its raw material composition includes the following components in mass percentage:
[0130] Metal powder: 55.2% flake silver powder, 36.8% spherical silver powder;
[0131] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0132] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0133] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0134] PANI / AgNPs additive: 0%, i.e. no addition.
[0135] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent and additive, first manually stirring, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0136] Comparative Example 2
[0137] This comparative example provides a polyaniline powder, the preparation method of which comprises:
[0138] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the reaction was stirred at 0-4°C for 11 hours. After the reaction was completed, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol and acetone, and the product was placed in a vacuum oven at 60°C and dried for 24 hours to obtain polyaniline powder.
[0139] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0140] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0141] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0142] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0143] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0144] Additive: 13%; the additive is the polyaniline powder provided in this comparative example.
[0145] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0146] Example 7
[0147] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0148] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0149] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0150] Metal powder: 16.4% flake silver powder, 16.4% spherical silver powder, 49.2% silver-coated copper powder;
[0151] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0152] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0153] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0154] PANI / AgNPs additive: 10%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0155] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0156] Example 8
[0157] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0158] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0159] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0160] Metal powder: 15.8% flake silver powder, 15.8% spherical silver powder, 47.4% silver-coated copper powder;
[0161] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0162] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0163] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0164] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0165] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0166] Example 9
[0167] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0168] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.1 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0169] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0170] Metal powder: 15.4% flake silver powder, 15.4% spherical silver powder, 46.2% silver-coated copper powder;
[0171] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0172] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0173] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0174] PANI / AgNPs additive: 15%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0175] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0176] Comparative Example 3
[0177] This comparative example provides a low-temperature slurry, and based on the mass of the low-temperature slurry being 100%, its raw material composition includes the following components in mass percentage:
[0178] Metal powder: 18.4% flake silver powder, 18.4% spherical silver powder, 55.2% silver-coated copper powder;
[0179] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0180] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0181] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0182] PANI / AgNPs additive: 0%, i.e. no addition.
[0183] The specific method includes: weighing the corresponding raw materials according to the mass percentage, mixing the metal powder, binder, solvent and additive, first stirring manually, and then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing through a three-roll mill for 6 times to obtain a low-temperature slurry.
[0184] Comparative Example 4
[0185] This comparative example provides a polyaniline / nanosilver composite material, the preparation method of which comprises:
[0186] 10mmol of aniline monomer was dissolved in 100mL of 0.1mol / L hydrochloric acid solution, 10mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol and acetone, and the product was dried in a vacuum oven at 60°C for 24h to obtain polyaniline powder. 10mmol of glucose, 0.34g of polyaniline powder and 0.05g of polyvinyl pyrrolidone were added into deionized water and stirred evenly, 10mmol of silver nitrate solution was added dropwise thereto, and the mixture was stirred in a water bath at 50°C for 10h. After the reaction, the product was separated by centrifugation, washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 60°C for 24h. The polyaniline / nanosilver powder was obtained by grinding, which is a polyaniline / nanosilver composite material.
[0187] Compared with the preparation methods of Examples 1 to 9, the method of this comparative example changes the acidic reaction medium to hydrochloric acid, and does not perform an acid doping reaction (ie, the second reaction) separately.
[0188] This comparative example also provides a low-temperature slurry, and based on the mass of the low-temperature slurry being 100%, its raw material composition includes the following components in mass percentage:
[0189] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0190] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0191] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0192] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0193] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this comparative example.
[0194] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0195] Comparative Example 5
[0196] This comparative example provides a polyaniline / nanosilver composite material, the preparation method of which comprises:
[0197] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A p-toluenesulfonic acid solution with a concentration of 0.1 M was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of p-toluenesulfonic acid solution and stirred at 30°C for 5 h for the second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0198] This comparative example also provides a low-temperature slurry, and based on the mass of the low-temperature slurry being 100%, its raw material composition includes the following components in mass percentage:
[0199] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0200] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0201] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0202] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0203] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this comparative example.
[0204] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0205] Example 10
[0206] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0207] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 hours. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 hours to obtain polyaniline powder. A 0.15 M HCl solution was prepared and stirred for 1 hour, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 hours for the second reaction. After the reaction, the product was vacuum filtered and dried in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10 mmol glucose, 0.34 g modified polyaniline powder and 0.05 g polyvinyl pyrrolidone were added to deionized water and stirred evenly, 10 mmol silver nitrate solution was added dropwise thereto, and the mixture was stirred in a 50°C water bath for 10 hours. After the reaction, the product was separated by centrifugation, washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 60°C for 24 hours. The polyaniline / nanosilver powder was obtained by grinding, which is a polyaniline / nanosilver composite material.
[0208] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0209] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0210] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0211] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0212] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0213] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0214] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0215] Embodiment 11
[0216] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0217] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed three times with deionized water, anhydrous methanol, and acetone. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.2 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for a second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol glucose, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0218] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0219] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0220] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0221] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0222] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0223] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0224] Example 12
[0225] This embodiment provides a polyaniline / nanosilver composite material, the preparation method of which includes:
[0226] 10 mmol of aniline monomer was dissolved in 100 mL of 0.1 mol / L sulfosalicylic acid solution, 10 mmol of ammonium persulfate solution was added dropwise thereto, and the mixture was stirred at 0-4°C for 11 h. After the reaction, the product was precipitated by vacuum filtration, and the product was washed with deionized water, anhydrous methanol and acetone for 3 times. The product was placed in a vacuum oven at 60°C and dried for 24 h to obtain polyaniline powder. A 0.15 M HCl solution was prepared and stirred for 1 h, and then 10 g of polyaniline was added to 30 g of HCl solution and stirred at 30°C for 5 h for the second reaction. After the reaction is completed, the product is vacuum filtered and placed in a vacuum oven at 60°C for 12 hours to obtain modified polyaniline powder; 10mmol sodium hypophosphite, 0.34g modified polyaniline powder, and 0.05g polyvinyl pyrrolidone are added to deionized water and stirred evenly, 10mmol silver nitrate solution is added dropwise thereto, and the mixture is stirred and reacted in a 50°C water bath for 10 hours. After the reaction is completed, the product is centrifuged and separated, and washed three times with deionized water and anhydrous ethanol by centrifugation, placed in a vacuum oven at 60°C for 24 hours, and ground to obtain polyaniline / nanosilver powder, which is a polyaniline / nanosilver composite material.
[0227] This embodiment also provides a low-temperature slurry. Taking the mass of the low-temperature slurry as 100%, the raw material composition includes the following components in mass percentage:
[0228] Metal powder: 47.4% flake silver powder, 31.6% spherical silver powder;
[0229] Binder: 1.3% thermoplastic polyurethane, 2.5% epoxy resin;
[0230] Solvent: 0.6% dibasic acid ester, 0.6% isophorone, 2% terpineol;
[0231] Additives: 0.2% 2-methylimidazole, 0.3% γ-aminopropyltrimethoxysilane, 0.2% polydimethylsiloxane, 0.3% polyethylene glycol;
[0232] PANI / AgNPs additive: 13%; the PANI / AgNPs additive is the polyaniline / nanosilver powder provided in this embodiment.
[0233] The preparation method of the low-temperature slurry comprises: weighing corresponding raw materials according to mass percentage, mixing metal powder, binder, solvent, auxiliary agent and additive, first stirring manually, then putting into a vacuum degassing machine for stirring at a speed of 2500rpm for 2min; finally grinding and dispersing by a three-roll mill for 6 times to obtain the low-temperature slurry.
[0234] Test Case
[0235] The low-temperature conductive silver pastes of the above embodiments and comparative examples were tested for related properties, and the specific tests included:
[0236] 1. Viscosity
[0237] The viscosity test was performed using a Brookfield viscometer at a speed of 10 rpm to test the viscosity value at 4 minutes.
[0238] 2. Resistivity test
[0239] The resistance at both ends of the sintered electrode body was tested using a four-probe ohmmeter.
[0240] 3. Ohmic contact resistance test
[0241] The slurry is applied on the heterojunction cell by a screen printer and then dried and solidified, and the contact resistance is measured using a contact resistance device.
[0242] 4. Curing temperature test
[0243] The electrodes printed on the cell are placed in an oven at a set temperature and cured for 30 minutes. The measured curing temperature is the temperature at which curing is completed within 30 minutes.
[0244] 5. Welding tensile test
[0245] The battery cell made of conductive silver paste is used as the sample, copper-based lead-tin soldering rod is selected, the temperature of the electric soldering iron is set to 350℃, and the tensile test machine is used for 180° uniform speed test, the tensile speed is 300mm / min, and the sample size is 166mm. The average value of the tensile test results is taken as the tensile value of this test. Five battery cells are tested for each sample, and then the average value is taken to obtain the tensile result of the sample.
[0246] The above test results are summarized in Table 1.
[0247] Table 1
[0248]
[0249] As can be seen from Table 1, compared with the low-temperature slurries of Examples 1 to 6, the low-temperature slurry of Comparative Example 1 does not add the PANI / AgNPs additive, and the viscosity and welding tension are significantly reduced, and the resistance is significantly increased. In particular, compared with Examples 2 to 4, the resistivity and contact resistance of Comparative Example 1 without adding PANI / AgNPs increase, and the welding tension also decreases. This result shows that the low-temperature slurry provided by the present invention can reduce the line resistance and contact resistance by adding PANI / AgNPs, and the curing temperature is below 200°C, and has good weldability.
[0250] It can be seen from Table 1 that compared with the low-temperature slurries of Examples 1 to 6, the additive in the low-temperature slurry of Comparative Example 2 is a single polyaniline powder, the body resistance and contact resistance are two orders of magnitude higher, and the viscosity is larger, and the welding tension is reduced. Combining the results of Examples 1 to 6 and Comparative Example 1, it can be seen that using only polyaniline as an additive cannot improve the performance of the low-temperature slurry, and only the synergistic effect of polyaniline and nanosilver can improve the comprehensive performance of the slurry.
[0251] In addition, it can be seen from the test results of Example 3 and Comparative Example 1 that the addition of PANI / AgNPs is conducive to reducing the silver content, and the resistivity and contact resistance are also reduced, and the solderability is better.
[0252] Comparing Example 1 with Comparative Example 1, it can be seen that the addition of PANI / AgNPs has a significant effect on the viscosity of the slurry. From the test results of Example 1 to Example 6, it can be seen that as the content of PANI / AgNPs increases, the viscosity of the system increases. This result shows that an appropriate increase in the amount of PANI / AgNPs will increase the viscosity, which is beneficial to printing.
[0253] Compared with the low-temperature paste of Comparative Example 2, the low-temperature pastes of Examples 7 to 9, in which no PANI / AgNPs additive is added, have increased resistivity and contact resistance, and decreased welding tension. In Examples 7 to 9, as the content of PANI / AgNPs increases, the viscosity increases, and the viscosity of the low-temperature paste of Example 7 is easier to print.
[0254] From the comparison between Comparative Example 4 and Example 3, it can be seen that the composite material prepared without the acid doping experiment (i.e., the second reaction) will significantly increase the resistance of the low-temperature slurry; from the comparison between Comparative Example 5 and Example 3, it can also be seen that the effect of using p-toluenesulfonic acid as a dopant is not as good as hydrochloric acid, resulting in an increase in the slurry resistance. The above effects show that the doping effect of using inorganic acid is worse than that of organic acid. Hydrochloric acid doping of polyaniline can effectively reduce the resistance of the low-temperature slurry prepared by the composite material. This is because the H generated by the decomposition of inorganic acid + and anions (such as Cl-, SO4 2- PO4 3- etc.), combining with the N atoms in the amine and imine groups to form poles and dipoles that are delocalized into the π bonds of the entire molecular chain, thus making polyaniline exhibit higher conductivity.
[0255] Compared with Example 3, Example 10 and Example 11 increased the amount of doping acid added, and the low-temperature slurry prepared thereby had lower resistance. This result shows that the resistivity of the low-temperature slurry can be reduced by appropriately increasing the amount of doping acid used in the present invention.
[0256] In Example 12, hypophosphorous acid with stronger reducing property is selected for reaction, and the low-temperature slurry prepared thereby has lower resistance. This result shows that the resistivity of the low-temperature slurry can be reduced by selecting an appropriate type of reducing agent in the present invention.
[0257] The above results show that the present invention can improve the conductivity and weldability of low-temperature slurry by adding polyaniline and the composite material of polyaniline to the low-temperature slurry, reduce the silver content in the slurry, and make the slurry solidify at a lower temperature. By controlling the content of additives in the slurry, the viscosity of the slurry can be optimized and the printing performance of the slurry can be improved.
Claims
1. A method for preparing a polyaniline / nanosilver composite material, the preparation method comprising: Aniline monomer, an acidic reaction medium, and an oxidant are mixed to form a first reaction system, and a first reaction is performed to obtain polyaniline; mixing polyaniline with a doping acid to form a second reaction system, and performing a second reaction to obtain modified polyaniline; The modified polyaniline is mixed with the first dispersant and the reducing agent, and then a silver source is added to form a third reaction system, and a third reaction is performed to obtain a polyaniline / nano-silver composite material.
2. The preparation method according to claim 1, wherein The acidic reaction medium includes one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid and hypophosphorous acid.
3. The preparation method according to claim 1, wherein The oxidant includes one or a combination of two or more of hydrogen peroxide, ammonium persulfate, ammonium peroxide, and potassium chlorate.
4. The preparation method according to claim 1, wherein The molar ratio of the aniline monomer to the oxidant is 0.1-1:1; The molar ratio of the acidic reaction medium to the aniline monomer is 0.1-1:
1.
5. The preparation method according to claim 1, wherein The temperature of the first reaction is -1°C to 10°C, and the time of the first reaction is 1h-15h.
6. The preparation method according to claim 1, wherein The doping acid includes one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid, and hypophosphorous acid; Preferably, the mass ratio of the doping acid to polyaniline is 0.01-1:
1.
7. The preparation method according to claim 1, wherein The temperature of the second reaction is 25° C.-55° C., and the time of the second reaction is 1 h-24 h.
8. The preparation method according to claim 1, wherein The silver source includes one or a combination of two or more of silver chloride, silver nitrate and potassium silver cyanide.
9. The preparation method according to claim 1, wherein: The mass ratio of the modified polyaniline to the silver source is 0.1-1:
1.
10. The preparation method according to claim 1, wherein: The first dispersant includes one or a combination of two or more of polyvinyl pyrrolidone, polyvinyl alcohol, and sodium dodecyl sulfate; The reducing agent includes one or a combination of two or more of sodium borohydride, hydrazine hydrate, glucose, ascorbic acid, sodium hypophosphite, and tannic acid; Preferably, the mass of the first dispersant is 1%-7% of the mass of the silver source, and the molar ratio of the reducing agent to the silver source is 0.5-3:
1.
11. The preparation method according to claim 1, wherein: The temperature of the third reaction is 25° C.-80° C., and the time of the third reaction is 1 h-10 h.
12. A polyaniline / nanosilver composite material obtained by the preparation method according to any one of claims 1 to 11.
13. A low-temperature slurry, based on the total mass of the low-temperature slurry being 100%, the low-temperature slurry comprises: Micro-nano powder: 72%-87%; Organic binder: 1%-3.8%; PANI / AgNPs additive: 5%-20%, preferably 5%-15%; Solvent: 1%-3.2%; Additives: 0.1%-1%; Wherein, the PANI / AgNPs additive comprises the polyaniline / nanosilver composite material as described in claim 12.
14. The low-temperature slurry according to claim 13, wherein: The micro-nano powder includes one or a combination of two or more of micro-nano spherical silver powder, micro-nano flaky silver powder, and micro-nano silver-coated copper powder; Preferably, the specific surface area of the micro-nano spherical silver powder is 0.4-0.6 m 2 / g、D 50 1.9-2.3μm; Preferably, the surface area of the micro-nano flaky silver powder is 0.55-0.8 m 2 / g、D 50 2.8-3.3μm; Preferably, the tap density of the micro-nano silver-coated copper powder is 2.8-5.4 g / cm 3 , D 50 4.2-5.7μm.
15. The low-temperature slurry according to claim 13, wherein: The organic binder includes one or a combination of two or more of phenolic resin, thermoplastic polyurethane, epoxy resin, silicone resin, urea-formaldehyde resin and acrylic resin.
16. The low-temperature slurry according to claim 13, wherein: The solvent includes one or a combination of two or more of terpineol, butyl carbitol, butyl carbitol acetate, dioctyl phthalate, dibasic acid ester, ethylene glycol butyl ether, diethylene glycol monomethyl ether, and isophorone.
17. The low-temperature slurry according to claim 13, wherein: The auxiliary agents include a curing agent, a coupling agent, a leveling agent and a second dispersant; The curing agent includes one or a combination of two or more of an imidazole curing agent, an amine curing agent, and an acid anhydride curing agent; The coupling agent includes one or a combination of two or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, bistriethanolamine diisopropyl titanate, and neoalkoxy tris(p-aminophenoxy) zirconate; The leveling agent includes one or a combination of two or more of polyether, polyorganosiloxane, polydimethylsiloxane, turpentine, and polyacrylic acid; The second dispersant includes one or a combination of two or more of oleic acid, stearic acid, ethyl acetoacetate, butyrylacetone, polyethylene glycol, hydrogenated castor oil, and polyamide wax.
18. A heterojunction battery made of the low-temperature slurry according to any one of claims 13 to 17.
Citation Information
Cited By
Ultraviolet-absorption corrosion-resistant super-hydrophobic PMMA (polymethyl methacrylate) coating and preparation method thereof
CN121108834A